2016
DOI: 10.1007/s00128-016-1891-7
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Content in Organs and Tissues of Indigenous (Vulpes vulpes L.) and Invasive (Nyctereutes procyonoides Gray.) Species of Canids from Areas Near Cherepovets (North-Western Industrial Region, Russia)

Abstract: Trophic and spatial components of ecological niches of two canids native Vulpes vulpes and introduced Nyctereutes procyonoides are overlapping partially in the studied region. Maximum concentrations of mercury in predatory mammals of Canidae family from surroundings of Cherepovets have been determined in liver and kidneys (over 0.50 mg/kg wet weight), with minimal concentrations in brain (<0.2 mg/kg wet weight). The amount of mercury in the same organs of the red fox and raccoon dog is not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…The level of mercury in the tissues of the fox from the area around a large metallurgical complex (Cherepovetsky district -3) is comparable to the concentration of mercury in the tissues of the fox from a specially protected natural area (Kirillovsky district -2) and an area significantly distant from industrial complexes (Verkhovazhsky district -1). The concentration of mercury in the muscles, liver and brain of foxes from the industrial region was confirmed by the data on the content of mercury in red foxes, previously studied in this area [13]. The average concentration of mercury in the muscles of the red fox from the Vologda region is 2 times higher than in the muscles of the fox from suburban areas of Croatia [4] and 3 times lower than in the muscles of the fox from regions contaminated with heavy metals in Spain, where for a long time there was a mining activity [15].…”
Section: Fig 2 the Concentration Of Mercury In The Tissues Of The Rsupporting
confidence: 76%
“…The level of mercury in the tissues of the fox from the area around a large metallurgical complex (Cherepovetsky district -3) is comparable to the concentration of mercury in the tissues of the fox from a specially protected natural area (Kirillovsky district -2) and an area significantly distant from industrial complexes (Verkhovazhsky district -1). The concentration of mercury in the muscles, liver and brain of foxes from the industrial region was confirmed by the data on the content of mercury in red foxes, previously studied in this area [13]. The average concentration of mercury in the muscles of the red fox from the Vologda region is 2 times higher than in the muscles of the fox from suburban areas of Croatia [4] and 3 times lower than in the muscles of the fox from regions contaminated with heavy metals in Spain, where for a long time there was a mining activity [15].…”
Section: Fig 2 the Concentration Of Mercury In The Tissues Of The Rsupporting
confidence: 76%
“…Obtained data on the distribution of mercury in amphibians matches with data from the literature on this issue: the maximum сontents of the metal are found in the liver and the kidneys, the minimal is seen in the muscles and skin [16]. Studies on mercury accumulation in organs and tissues of mammals also show the maximal mercury сontent to be found in the liver and kidneys, in other words, in the organs that perform the function of detoxification [17], [18], [19].…”
Section: Fig 2 the сOntent Of Mercury In The Tissues Of Amphibiasupporting
confidence: 68%
“…It is, therefore, necessary to trace the presence and the number of chemical substances, such as heavy metals and pesticides, in their tissues. Contaminants studies make it possible to understand the organic changes in the animal, but also the potential dangers for human health [13,14]. Contaminants' exposition, during long times and at low doses, can alter physiological processes (e.g., metabolism, hormonal changes), decrease animal body condition (e.g., small and weak animals), immunotoxic effects, decrease reproductive success (e.g., infertility, abortion, malformations), and can result in genotoxic and mutagenic effects (cancer) [8,15,16].…”
Section: Red Fox As a Sentinel Of Environmental Contaminationmentioning
confidence: 99%